SEJARAH QIRĀ’AT AL-QUR’AN DALAM PERSPEKTIF LINTAS MADZHAB - Harun Qadaru Ramadhan; Gustiar Abduloh; Kerwanto (EL-ADABI : Jurnal Studi Islam, 2023)
Qirā'at is one of the disciplines of the Koran which is quite classic. This knowledge is known as the different ways of reading the Koran. Across schools of thought, we will see the diversity of viewpoints regarding this discipline, starting from Sunni, Shia and Orientalist thought. The discussion in this paper starts from the history, origins, scope of knowledge from a cross-school perspective, as well as the views of figures representing each sect (madhzhab).